Integrated Yoga and Naturopathy Approach in the Management of SciaticaACase Report - K, Jeyashree; M, Pandiaraja (Indian Journal of Integrative Medicine, 2024)
Sciatica is the painful debilitating condition characterized by excruciating pain, numbness, tingling or burning sensation over thedermatomal course of sciatic nerve distribution. Globally its prevalence is about 1.2 to 43%. It is usually caused by nerve r ootcompression or irritation, disc herniation, vascular anomalies, muscular or bony compression. We report the case of 50 year old malewith the complaint of low back pain associated with pain radiating to left leg . On the basis of clinical examination the case wasdiagnosed as sciatica. Yoga and Naturopathy intervention s w ere given for 7 days in outpatient ward. After the intervention the paingradually decreased . VAS reduced from 10 to 4. SFI score reduced from 19 to SBI score reduced from 23 to 13. The VAS Scaleand SBI and SFI showed improvement in scores. No adverse ef fects were observed during the treatment. Yoga and naturopathy havebeen shown to decrease the pain , bothersomeness and frequency of symptoms . Hence this study can be done with large sample size infuture with longer duration of course of treatment.